TREATMENT OF EATING DISORDERS WITH NUTRITION - Abdulaziz Mohammed Alhussini, Abdullah Mohammed Alahmed, Abdullah Ali Abdullah Aldhafyan, Waleed Ibrahim Nasr Almusabehi, Mohammed Omar Alateeq, Yasser Mahdi Al-Abdoon, Muhammad Abdulaziz Nasser Al-Mufarrej, ,; Tamran Mohammed Hamad Altamran, Sulaiman Abdullah Al Dowaihi, Mohammed Faleh Alharbi, Uthman Mohammed Alnowihl, Yasser Mahdi Al-Abdoon, Jeza Mahdi Zaiyed Alotaibi, (Chelonian Research Foundation, 2022)
The multidisciplinary clinical team that treats patients with eating disorders must include nutritionists. Their knowledge and proficiency encompass nutrition, physiology, and the ability to encourage behavioral modifications concerning the psycho-socio-cultural facets of eating habits. The state of the art in nutrition therapy for eating disorders is summarized in this review, along with recommendations for nutrition assessment, interventions, information and data monitoring and interpretation, awareness of emerging roles for nutrition, and crucial considerations for professional boundaries in the eating disorders field. Education and background in nutrition therapy.particular to eating disorders encourage a favorable outcome for patients. Nutritionists work at all levels of care, providing outpatient, partial hospitalization, inpatient, and residential programs as well as individual and group treatment. To discuss individual-specific nutrition factors is outside the purview of this essay. To identify the best effective nutrition therapy options for treating eating disorders, more study is required. (2010) Nutr Clin Pract. 25:122–136 Keywords: Multidisciplinary, Nutritional therapy, CBT, Refeeding syndrome, Micronutrient deficiencies